Analisis Minat Berwirausaha Bidang Teknik Pendingin dan Tata Udara Siswa Sekolah Menegah Kejuruan - Rahmad Kurnia; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The increase number of unemployed every year is not in line with the opening of job opportunities, the highest unemployment rate even comes from vocational school graduates, so being an entrepreneur is the best solution to compete in the midst of intense job competition. The scientific competence in the field of refrigeration and air conditioning engineering that students have is also one of the basic opportunities for entrepreneurship by paying attention to the factors that encourage it. The factors that encourage entrepreneurial interest come from internal and internal factors of an individual. Therefore, this study aims to determine how much entrepreneurial interest in the field of Refrigeration and Air Conditioning Engineering students at SMK N 1 West Sumatra is in terms of internal and external factors. The type of research used is descriptive research with a quantitative approach. The subjects in this study were students of class XI and XII with a total of 37 samples of Cooling and Air Conditioning Engineering at SMK N 1 West Sumatra. Data collection techniques using a questionnaire using the google form platform. The data is processed using SPSS to get the percentage value of the respondents' achievement for the interest in entrepreneurship. The results showed that the percentage of TCR for entrepreneurial interest in terms of students' internal and external factors was high, and based on internal factors students' entrepreneurial interest was high, and from external factors students' entrepreneurial interest was in the sufficient category. So it can be concluded that students of Cooling and Air Conditioning Engineering Expertise competence have a high entrepreneurial interest and are dominated by students' internal factors.